ONLINE ACCESS TO THE TOPIC OF FLUID FLOW AND BIOPHYSICAL PROPERTIES FOR STUDENTS OF MEDICAL INSTITUTES - Ilhom Juraev Gulomovich; Hudaykulova Shoira Narzullaevna; Arzibekov Ulugbek Rahmonkulovich; Askar Jangibaevich Ergashev; Husan Muhiddinovich Jalilov (International Journal of Innovations in Engineering Research and Technology, 2021)
This article is devoted to the transition of students of medical institutes in the modular system of lectures, practical classes and independent work on "Flow of fluids and biophysical properties." The importance of the viscosity coefficient in medicine, its application in diagnosis and forensic medical examination, the Stokes method of finding the viscosity coefficient, the availability of viscometric methods, and the use of the Gess (VK-4) viscometer in medicine to find the viscosity coefficient. It is also shown that the coefficient of surface tension is obtained by the method of drop break and the role of the surface tension coefficient in medicine.